2011
DOI: 10.1002/jwmg.110
|View full text |Cite
|
Sign up to set email alerts
|

Effects of mesopredators and prescribed fire on hispid cotton rat survival and cause‐specific mortality

Abstract: Control of mid‐sized mammalian predators (hereafter, mesopredators) is sometimes advocated in an attempt to reduce their impact on wildlife populations, particularly economically important (i.e., game) or endangered species. However, mesopredators may play a role in regulating small mammal populations; thus, lethal control of mesopredators may have unintended consequences. The hispid cotton rat (Sigmodon hispidus; hereafter, cotton rat) is one of the most common small mammals in the southeastern United States … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
54
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 30 publications
1
54
0
Order By: Relevance
“…That is, although the invasive predator's population density may remain stable, there is a shift in behaviour such that native fauna are more likely to be depredated when invasive predators co-occur with the threat. For example, predation rates of hispid cotton rats Sigmodon hispidus increased following prescribed fire in Georgia, USA (Conner et al, 2011). This is a 'functional' impact of invasive predators, as their impact on native prey populations is independent of their population density (Didham et al, 2007).…”
Section: Interactions Between Threatsmentioning
confidence: 98%
“…That is, although the invasive predator's population density may remain stable, there is a shift in behaviour such that native fauna are more likely to be depredated when invasive predators co-occur with the threat. For example, predation rates of hispid cotton rats Sigmodon hispidus increased following prescribed fire in Georgia, USA (Conner et al, 2011). This is a 'functional' impact of invasive predators, as their impact on native prey populations is independent of their population density (Didham et al, 2007).…”
Section: Interactions Between Threatsmentioning
confidence: 98%
“…However, these two threatening processes are often studied independently rather than as drivers that interact synergistically; few studies have focused on their possible interactions, and indirect effects on species declines that may occur as a result of these interactions (Hobbs 2001;Didham et al 2005Didham et al , 2007Brook et al 2008;Chalfoun & Martin 2009;Conner et al 2011;McGregor et al 2014;Hradsky et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Variability in vegetation structure influences the outcome of predator-prey interactions because predation risk and hunting success can be affected by attributes of the habitat occupied by both predator and prey (Moreno et al 1996;Janssen et al 2007;Chalfoun & Martin 2009;Conner et al 2011;McDonald et al 2016;Hradsky et al 2017). For example an experiment investigating the short-term effects of a prescribed fire on the red fox (Vulpes vulpes) and feral cat (Felis catus) and their native mammalian prey in southeastern Australia found that under prefire conditions invasive predators were more likely to occur at sites with an open understory, whereas most small-and medium-sized native mammals were positively associated with understory cover.…”
Section: Introductionmentioning
confidence: 99%
“…We expected bobcats to select for areas with lower basal areas managed by frequent fire that contained an abundance of understory vegetation. Selection of young pines in the Mississippi studies was primarily due to relative abundance of small mammals in young pines (Conner 1991, Conner et al 1992. Many young pines in our study area contained little herbaceous vegetation and few small mammals (Golley et al 1965, Schnell 1968, McMurry et al 1994, Masters et al 1998, which may explain why bobcats were farther from young pines.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, frequent use of prescribed fire in longleaf pine forests increases understory plant species richness, diversity, and evenness (Brockway and Lewis 1997), which may influence where bobcats search for prey items. Small mammals (e.g., cotton rats [Sigmodon hispidus], Conner et al 2011, Morris et al 2011 are commonly exposed to predation from bobcats and other predators following a fire event due to reductions in herbaceous cover. Our results may also be due to the scale of fire relative to bobcat home ranges.…”
Section: Discussionmentioning
confidence: 99%